Mixture design as a potential tool in modeling the effect of light wavelength on Dunaliella salina cultivation: an alternative solution to increase microalgae lipid productivity for biodiesel production - Bredda, Eduardo Henrique [UNESP]; Da Silva, Aneirson Francisco [UNESP]; Silva, Messias Borges [UNESP]; Da Rós, Patrícia Caroline Molgero (Taylor & Francis, 2020)
For a feasible microalgae biodiesel, increasing lipid productivity is a key parameter. An important cultivation parameter is light wavelength (λ). It can affect microalgal growth, lipid yield, and fatty acid composition. In the current study, the mixture design was used as an alternative to model the influence of the λ on the Dunaliella salina lipid productivity. The illumination was considered to be the mixture of different λ (the light colors blue, red, and green). All experiments were performed with and without sodium acetate (4 g/L), as carbon source, allowing the identification of the impact of the cultivation regimen (autotrophic or mixotrophic). Without sodium acetate, the highest lipid productivity was obtained using blue and red light. The use of mixotrophic cultivations significantly enhanced the results. The optimum obtained result was mixotrophic cultivation under 65% blue and 35% green light, resulting in biomass productivity of 105.06 mgL−1day−1, a lipid productivity of 53.47 mgL−1day−1, and lipid content of 50.89%. The main fatty acids of the oil obtained in this cultivation were oleic acid (36.52%) and palmitic acid (18.31%).
Keywords: Dunaliella salina; fatty acid profile; lipid productivity; optimization; simplex centroid mixture design